Zebrafish embryonic explants undergo genetically encoded self-assembly - Alexandra Schauer; Diana Pinheiro; Robert Hauschild; Carl-Philipp Heisenberg (eLife, 2020)
Embryonic stem cell cultures are thought to self-organize into embryoid bodies, able to undergo symmetry-breaking, germ layer specification and even morphogenesis. Yet, it is unclear how to reconcile this remarkable self-organization capacity with classical experiments demonstrating key roles for extrinsic biases by maternal factors and/or extraembryonic tissues in embryogenesis. Here, we show that zebrafish embryonic tissue explants, prepared prior to germ layer induction and lacking extraembryonic tissues, can specify all germ layers and form a seemingly complete mesendoderm anlage. Importantly, explant organization requires polarized inheritance of maternal factors from dorsal-marginal regions of the blastoderm. Moreover, induction of endoderm and head-mesoderm, which require peak Nodal-signaling levels, is highly variable in explants, reminiscent of embryos with reduced Nodal signals from the extraembryonic tissues. Together, these data suggest that zebrafish explants do not undergo bona fide self-organization, but rather display features of genetically encoded self-assembly, where intrinsic genetic programs control the emergence of order.